2015
DOI: 10.1002/lary.25505
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mandibular advancement appliances in treating obstructive sleep apnea syndrome: A systematic review

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 44 publications
2
59
2
Order By: Relevance
“…Third, a systematic review comparing adjustable with fixed devices or custom‐made devices with prefabricated ones showed that in both cases the former were more effective …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a systematic review comparing adjustable with fixed devices or custom‐made devices with prefabricated ones showed that in both cases the former were more effective …”
Section: Discussionmentioning
confidence: 99%
“…Third, a systematic review comparing adjustable with fixed devices or custom-made devices with prefabricated ones showed that in both cases the former were more effective. 51 Finally, there is a notable disparity with respect to some variables such as the time of follow-up, type of We have considered all of these factors when comparing our results with other studies in moderate-to-severe OSA patients.…”
Section: Effect Of the Mad On Polysomnographic Variablesmentioning
confidence: 98%
“…They also presented the results grouped by grade of severity and noted that in mild OSA, the effects of the two types of appliances were similar. In a systematic review, Serra-Torres et al [5] concluded that adjustable and custom-made mandibular advancement appliances give better results than fixed and prefabricated appliances, and that monobloc appliances give rise to more adverse events. Objective polygraphic registrations are crucial as described by Marklund et al [14] who evaluated fixed OAs incrementally advanced in response to the clinical observation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to the findings of a retrospective study by Lettieri et al [4], who found significant advantages in AHI reduction with adjustable compared with fixed appliances. In a systematic review, Serra-Torres et al [5] also concluded that adjustable and custom-made mandibular advancement appliances give better results than fixed and prefabricated appliances, and that monobloc appliances give rise to more adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…The articles were classified as being of high, medium or low quality according to the CONSORT criteria (11) adapted by Mattos et al (12) and used by Fernández-Ferrer et al and Serra-Torres et al (13,14). The quality of the systematic reviews was assessed in accordance with the PRISMA guidelines (10).…”
Section: Methodsmentioning
confidence: 99%